Investigating the Effect of Thermal Annealing Process on the Photovoltaic Performance of the Graphene-Silicon Solar Cell - Lifei Yang; Xiaolei Wu; Xin Shen; Xuegong Yu; Deren Yang (International Journal of Photoenergy)
Graphene-silicon (Gr-Si) Schottky solar cell has attracted much attention recently as promising candidate for low-cost photovoltaic application. For the fabrication of Gr-Si solar cell, the Gr film is usually transferred onto the Si substrate by wet transfer process. However, the impurities induced by this process at the graphene/silicon (Gr/Si) interface, such as H2O and O2, degrade the photovoltaic performance of the Gr-Si solar cell. We found that the thermal annealing process can effectively improve the photovoltaic performance of the Gr-Si solar cell by removing these impurities at the Gr/Si interface. More interestingly, the photovoltaic performance of the Gr-Si solar cell can be improved, furthermore, when exposed to air environment after the thermal annealing process. Through investigating the characteristics of the Gr-Si solar cell and the properties of the Gr film (carrier density and sheet resistance), we point out that this phenomenon is caused by the natural doping effect of the Gr film.